First record of a Lessepsian migrant: the sea cucumber Holothuria (Theelothuria) hamata Pearson, 1913 - Aydin, Mehmet; Gurlek, Mevlut; Samyn, Yves; Erguden, Deniz; Turan, Cemal (Zootaxa, 2019)
First record of a Lessepsian migrant: the sea cucumber Holothuria (Theelothuria) hamata Pearson, 1913. A single specimen of the Indo-West Pacific sea cucumber Holothuria (Theelothuria) hamata Pearson, 1913 has been captured in 2017 in the Mediterranean Sea, Turkey, Iskenderun Bay, at 30 m depth. This specimen is here described, and the taxonomy of the species is briefly discussed. Despite the lack of timed biogeographic evidence, we here argue that H. hamata is a Lessepsian migrant; the first in its genus and only the second holothuroid.